Perpaduan Kurikulum Bahasa Arab Salaf-Khalaf - Khabibi Muhammad Luthfi; Eva Farhah; Reza Sukma Nugraha; Tri Yanti Nurul Hidayati (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2022)
Purpose- This article aims to examine the combination of the classical dan modern Arabic curriculum at the Darul Hidayah Islamic Boarding School, Pati. Design/Methodology/Approach- This article uses an educational linguistic approach and qualitative-verification with curriculum organization theory. Data sourced from the field through observation, interviews and documentation, and analyzed using the Spradley method with domain, taxonomy, componential and cultural techniques. Findings- The results of this study are the combination of the Islamic boarding school curriculum in the form of a micro that integrates the curriculum of the classical dan modern Islamic boarding school, without linking it with other educational institutions. The integrated curriculum components are system, organization, objectives, materials, methods, educators dan evaluation. However, there are several sub-components that are not integrated, but only adopted from one of the classical dan modern Islamic boarding school. In addition to micro, in terms of planning dan learning practices, this curriculum blend is also integration-interconnection. Research Limitations/Implications- The field data of this research is only sourced from the Darul Hidayah Islamic boarding school, then the literature is compared with other Islamic boarding school.